Diagnosis of Corm Rot Disease of Taro: Case Study at Maybrat - West Papua - Paulus Woyen; Meity Suradji Sinaga; Efi Toding Tondok; Bonny Poernomo Wahyu Soekarno (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2020)
Diagnosis of Corm Rot Disease of Taro: Case Study at Maybrat - West Papua Taro (Colocasia esculenta L. Schott) is a herbaceous plant that has been used as food crop in some countries. It is believed that taro has originated from Southeast Asia (Lebot et al. 2010). In Maybrat, West Papua taro was used as a primary important staple food crop for ages by local tribes, and it is called Awiah or Wiah in this area. Until 2013, there is no proper pests and diseases problem reported in this area, but, in the middle of 2013 the local farmers reported an epidemic of corm rot disease on their taro crops. The aim of this study was to identify the causal agent of corm rot disease of taro in Maybrat. For disease diagnosis, pathogen isolation was carried out on samples of rotted corm collected from local farmers in Maybrat and followed by Koch Postulate. The assay was carried out in vivo and in planta to identify the corm rot pathogen. Out of 38 fungi isolated from the diseased corms, 50% of these were pathogenic. Three isolates called Y1, YP1, and S4 were able to cause corm rotting in vivo and root damage in planta. In planta assay showed that, combination of these isolates could cause severely root damage. Morphologically, isolate YP1 and S4 were identified as Fusarium oxysporum, while isolate Y1 was comfirmed genetically as F. solani. This is the first report of taro corm rot disease from Maybrat, West Papua.